Anxiety Status and its Relationship with General Health Related Quality of Life among Prostate Cancer Patients in Two University Hospitals in Kuala Lumpur, Malaysia. - Mohamad Rodi Isa; Foong Ming Moy; Azad Hassan Abdul Razack; Zulkifli Md Zainuddin; Nur Zuraida Zainal (Tehran University of Medical Sciences, 2013)
This study aimed to determine the prevalence of anxiety among prostate cancer patients, and to ascertain the association between stress status, socio-demographic, medical and surgical illness, current urinary problem and cancer status with general health-related quality of life (HRQOL) among these patients.A hospital based, cross sectional study was conducted at Surgical Clinic, University Malaya Medical Centre (UMMC) and Universiti Kebangsaan Malaysia Medical Centre (UKMMC) using universal sampling.A total of 193 patients were recruited. The prevalence of anxiety was 25.4% (95%CI: 19.2 - 31.6). The anxiety ratings were mild anxiety (10.4%), moderate anxiety (13.6%) and severe anxiety (1.6%). The total quality of life among stress group was 59.2 ± 14.7 and among non-stress group was 73.9 ± 12.7. There was a significant negative weak correlation between anxiety score and total quality of life (rs=-0.534, P